BENTURAN GLOBALISASI : PENGIKISAN MORAL BANGSA - Pratama, Nabella Yaniariza Putri; Anggraeni Dewi , Dinie (Jurnal Pendidikan Kewarganegaraan Undiksha, 2023)
Abstract : This study aims to provide an overview of the impact of globalization on the Indonesian nation, especially for the younger generation, who are currently deprived of morale due to the impact of globalization. This research method uses a qualitative approach with literature review methods and several case studies. The informants of this research come from several scientific journals, electronic books, and other sources whose accuracy has been confirmed by data collection techniques in the form of document studies. The results show that the impact of globalization has a very big influence on the morale of the Indonesian people. Globalization makes Indonesian people have a lifestyle that is not in accordance with the values embedded in Pancasila. There are so many impacts caused by globalization, especially for the future generations of the nation who always follow the flow of globalization without being able to filter the positive and negative impacts. By conducting this research, it is hoped that the Indonesian people, especially the nation's future young generation, will be able to know, sort out, and avoid the negative impacts of globalization that enter Indonesia freely.Keywords: the impact of globalization, national morals, the younger generation, Pancasila values